Morphological and Molecular Study of the Fish Parasitic Crustaceans Cymothoa indica and Mothocya collettei (Isopoda: Cymothoidae), with New Distribution Records - Hiroki Fujita (Diversity, 2023)
Cymothoidae are parasitic isopods that infest fishes inhabiting marine, brackish, and fresh-water environments. The systematics, distribution, and host specificity of cymothoids is often unknown. In this study, morphological observations and molecular analysis using the COI and 16S rRNA genes were conducted on a juvenile individual of Cymothoa indica infesting the wide-banded hardyhead silverside, Atherinomorus lacunosus, and an ovigerous female of Mothocya collettei infesting the hound needlefish, Tylosurus crocodilus, both collected from Okinawa Island, Japan. This is the first time that these two species of cymothoid have been collected in the Ryukyu Islands, and the juvenile C. indica in particular represents a new northern range limit for its species. That specimen was identified using molecular analysis and showed almost identical morphology to previously reported juveniles, but it differed in the numbers of robust setae on pereopods 6 and 7. The ovigerous female of M. collettei showed a high morphological similarity to M. collettei but had some morphological traits consistent with Mothocya affinis. DNA analysis indicated that these two nominal species of Mothocya are very closely related, and morphological and molecular studies using larger populations of both are needed.